Венок из сказа: круглый фантастический маршрут по пластам наррации между иронией и наивностью (по материалам Исаака Бабеля, Татьяны Толстой и Жоржи Амаду) - Aloe, Stefano (My University, 2012)
The essay tries to trace a path along some of the mechanisms of skaz following the works of very different authors: Tat’jana Tolstaja’s Kys, Isaak Babel’s tales and Jorge Amado’s Captains of the Sand. The joining aspect between these works must be found in the writers’ common attitude of permitting the characters and the internal narrator to directly convey their own points of view, while the author eclipses him or herself in a very hidden position. The reader has to reconstruct the author’s point of view by awakening his or her presence in the text, which is hinted at implicitly by irony, nostalgy, etc. Especially irony acts as a veiled link between the author and the reader, who percives his or her self-exclusion from the hic et nunc of the narration and from the characters’ skaz: irony underlines this unreachable distance and separates the reader from the naive narrator as well as taking the author away from his or her narrator.
A garland from skaz: a fantastic circular path across the levels of narration, between irony and naiveness (with examples by Isaak Babel, Tat’jana Tolstaja and Jorge Amado)
Wianek ze skazu: cyrkularna fantastyczna wędrówka po płaszczyznach narracji między ironią a naiwnością (na przykładzie Izaaka Babla, Tatiany Tołstoj i Jorge Amado)